Plant community characteristics and soil status in different land use systems in Dimapur district, Nagaland, India - Singh, Sudhir; Ahirwar, Saroj; Aier, Benjongwapang; Kanduri, Vinod; Kumar, Kewat (Leśne Prace Badawcze, 2012)
The main objective of this paper was to evaluate characteristics of plant community and the present status of soil in natural forest, home garden as well as agroforestry and shifting cultivation. We adopted a very well defined standard methodology for assessing various properties of soil. Plant community attributes were determined for different land use systems. The results showed that the importance value index (IVI) was the highest for natural forest, and then for agroforestry system, home garden while shifting cultivation indicated the least value of IVI. The study clearly shows that soil pH, organic matter content, total nitrogen, calcium, magnesium, and phosphorous under the conditions of the land use systems observed differ significantly from those in natural forest. The changes of topsoil properties and plant characteristics are very distinctive in shifting cultivation (jhuming system, i.e. slash-and-burning farming practice in hilly areas). Thus, the results obtained indicate that once natural forest has been removed, the soil-vegetation system is disrupted significantly. The results of this study reveal that shifting cultivation system has negative impact on environment in the region. Furthermore, the land use study carried out based on remote sensing showed that the area of settlement over natural forest has been increasing for last three decades, which results in many environmental problems such as loss of biodiversity, water and soil as well as air pollution.